2007
DOI: 10.1108/03074350710739623
|View full text |Cite
|
Sign up to set email alerts
|

A dividend function for Greek manufacturing

Abstract: PurposeIn this article an attempt is made to measure the amount of dividends allocated each year to shareholders in the large scale Greek manufacturing (establishments employing more than ten people).Design/methodology/approachThe construction of a dividend function is made and the factors affecting dividend distribution in Greece are discussed.FindingsWhile the original model provides for the effect of dividend taxation parameters – in addition to income considerations – in payout decisions, it is finally pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The coefficient of EPS has a positive sign, as hypothesized, and is statistically significant. These findings are consistent with those reported by Jensen et al (1992), Aivazian et al (2003, 2006), Wei et al (2003), Amidu and Abor (2006), DeAngelo et al (2006), Anastassiou (2007), Bodla et al (2007), Pandey and Bhat (2007), and Andres et al (2009).…”
Section: Empirical Results and Discussionsupporting
confidence: 93%
“…The coefficient of EPS has a positive sign, as hypothesized, and is statistically significant. These findings are consistent with those reported by Jensen et al (1992), Aivazian et al (2003, 2006), Wei et al (2003), Amidu and Abor (2006), DeAngelo et al (2006), Anastassiou (2007), Bodla et al (2007), Pandey and Bhat (2007), and Andres et al (2009).…”
Section: Empirical Results and Discussionsupporting
confidence: 93%
“…However, a number of studies, including Glen et al (1995), Aivazian et al (2003b) and Anastassiou (2007), have reported that Lintner's model does not work well in the context of emerging markets.…”
Section: Research Methodology Hypothesesmentioning
confidence: 94%